The Effect of Visual Cues on Difficulty Ratings for Segregation of Musical Streams in Listeners with Impaired Hearing - Innes-Brown, Hamish (Public Library of Science, 2011)
BACKGROUND: Enjoyment of music is an important part of life that may be degraded for people with hearing impairments, especially those using cochlear implants. The ability to follow separate lines of melody is an important factor in music appreciation. This ability relies on effective auditory streaming, which is much reduced in people with hearing impairment, contributing to difficulties in music appreciation. The aim of this study was to assess whether visual cues could reduce the subjective difficulty of segregating a melody from interleaved background notes in normally hearing listeners, those using hearing aids, and those using cochlear implants. METHODOLOGY/PRINCIPAL FINDINGS: Normally hearing listeners (N = 20), hearing aid users (N = 10), and cochlear implant users (N = 11) were asked to rate the difficulty of segregating a repeating four-note melody from random interleaved distracter notes. The pitch of the background notes was gradually increased or decreased throughout blocks, providing a range of difficulty from easy (with a large pitch separation between melody and distracter) to impossible (with the melody and distracter completely overlapping). Visual cues were provided on half the blocks, and difficulty ratings for blocks with and without visual cues were compared between groups. Visual cues reduced the subjective difficulty of extracting the melody from the distracter notes for normally hearing listeners and cochlear implant users, but not hearing aid users. CONCLUSION/SIGNIFICANCE: Simple visual cues may improve the ability of cochlear implant users to segregate lines of music, thus potentially increasing their enjoyment of music. More research is needed to determine what type of acoustic cues to encode visually in order to optimise the benefits they may provide.